Transcriptome network analysis identifies protective role of the LXR/SREBP-1c axis in murine pulmonary fibrosis - Shichino, Shigeyuki; Ueha, Satoshi; Hashimoto, Shinichi; Otsuji, Mikiya; Abe, Jun; Tsukui, Tatsuya; Deshimaru, Shungo; Nakajima, Takuya; Kosugi-Kanaya, Mizuha; Shand, Francis H.W.; Inagaki, Yutaka; Shimano, Hitoshi; et al. (JCI insight, 2019)
Pulmonary fibrosis (PF) is an intractable disorder with a poor prognosis. Although lung fibroblasts play a central role in PF, the key regulatory molecules involved in this process remain unknown. To address this issue, we performed a time-course transcriptome analysis on lung fibroblasts of bleomycin- and silica-treated murine lungs. We found gene modules whose expression kinetics were associated with the progression of PF and human idiopathic PF (IPF). Upstream analysis of a transcriptome network helped in identifying 55 hub transcription factors that were highly connected with PF-associated gene modules. Of these hubs, the expression of Srebf1 decreased in line with progression of PF and human IPF, suggesting its suppressive role in fibroblast activation. Consistently, adoptive transfer and genetic modification studies revealed that the hub transcription factor SREBP-1c suppressed PF-associated gene expression changes in lung fibroblasts and PF pathology in vivo. Moreover, therapeutic pharmacological activation of LXR, an SREBP-1c activator, suppressed the Srebf1-dependent activation of fibroblasts and progression of PF. Thus, SREBP-1c acts as a protective hub of lung fibroblast activation in PF. Collectively, the findings of the current study may prove to be valuable in the development of effective therapeutic strategies for PF.